2017
DOI: 10.1021/acschembio.7b00142
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-Based Inhibition of the Mycobacterium tuberculosis Branched-Chain Aminotransferase by d- and l-Cycloserine

Abstract: The branched-chain aminotransferase is a pyridoxal 5′-phosphate (PLP)-dependent enzyme responsible for the final step in the biosynthesis of all three branched-chain amino acids, L-leucine, L-isoleucine, and L-valine, in bacteria. We have investigated the mechanism of inactivation of the branched-chain aminotransferase from Mycobacterium tuberculosis (MtIlvE) by D- and L-cycloserine. D-Cycloserine is currently used only in the treatment of multidrug–drug-resistant tuberculosis. Our results show a time-and conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 60 publications
3
35
0
Order By: Relevance
“…However, although our results confirm that Asp is indeed a nitrogen source, they also demonstrate that, of the tested amino acids, Gln is the principal source of nitrogen for intracellular Mtb and is the amino acid whose nitrogen is most widely assimilated (Figure 1C). Gln is the major fuel for a variety of mammalian cells including macrophages (Zhang et al., 2017), and THP-1 macrophages have previously been shown to assimilate Gln into Glu (Amorim Franco et al., 2017, Zhao et al., 2013, Choi and Park, 2018). Our previous study demonstrated that carbon from both Glu and Gln was available to Mtb inside the macrophage (Beste et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, although our results confirm that Asp is indeed a nitrogen source, they also demonstrate that, of the tested amino acids, Gln is the principal source of nitrogen for intracellular Mtb and is the amino acid whose nitrogen is most widely assimilated (Figure 1C). Gln is the major fuel for a variety of mammalian cells including macrophages (Zhang et al., 2017), and THP-1 macrophages have previously been shown to assimilate Gln into Glu (Amorim Franco et al., 2017, Zhao et al., 2013, Choi and Park, 2018). Our previous study demonstrated that carbon from both Glu and Gln was available to Mtb inside the macrophage (Beste et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…137 This reaction is reversible and depends on the coenzyme PLP being covalently bound to the enzyme through a Schiff base with a protein lysine residue. 138 The first three-dimensional structure of a bacterial BCAT was reported in 1997.…”
Section: Ilve Branched-chain Aminotransferasementioning
confidence: 99%
“…A similar feature was observed when Mt IlvE was inhibited by d - and l -cycloserine. 137 d -Cycloserine is a second-line drug used in the treatment of MDR-TB and inhibits two sequential reactions of the peptidoglycan biosynthetic pathway: the PLP-dependent alanine racemase and d -alanine- d -alanine ligase. 149 Mt IlvE is inhibited by both cycloserine isomers in a time- and concentration-dependent fashion.…”
Section: Ilve Branched-chain Aminotransferasementioning
confidence: 99%
See 1 more Smart Citation
“…Alanine racemase, an enzyme that performs racemization of l ‐alanine to d ‐alanine is involved in peptidoglycan biosynthesis. d ‐Cycloserine, a second line TB drug inhibits alanine racemase, d ‐alanine ligase, and l ‐alanine dehydrogenase enzymes from M. tuberculosis .…”
Section: Screening Approachesmentioning
confidence: 99%